STUDY OF IMMOBILIZATION OF PROTEASE AND SORPTION OF BSA ON CELLULOSE, CELLULOSE DERIVATIVES, AND GRAFT COPOLYMERS - Rajeev Kumar Sharma; Jashbir Singh; Ghanshyam S. Chauhan (BioResources, 2010)
In order to develop novel polymeric supports based on cellulosics, cellulose extracted from pine needles, a perennial resource material available in huge quantities as waste, was graft copolymerized with vinyl monomers. Cellulose, cellulose derivatives, and their graft copolymers with highest percent grafting (Pg) were used as supports for immobilization of an industrially important protease enzyme and the protein bovine serum albumin (BSA) by a specific sorption method. The Manachini method was used to determine activity of the immobilized enzyme. Sorption of protein was characterized by activity of protein concentration by the Lowry method. Cellulose itself was found to be effective as a polymeric support to retain a good amount of protease and BSA, whereas cellulose derivatives were effective to adsorb BSA only. Among cellulose graft copolymers, those based on methyl methacrylate proved to be better sorbents.